Development of surface plasmon resonance sensor using carbon-based nanomaterials and chitosan for dopamine detection - Kamal Eddin, Faten Bashar (2023)
Dopamine (DA) plays a vital role in the brain and central nervous system. Therefore, there is a great need to develop a sensitive and selective sensor to monitor and determine DA concentrations for diagnostic purposes and diseases prevention. Up to now, employing surface plasmon resonance (SPR) sensors in DA determination is very limited, and its utilization to detect analytes with low concentrations still needs sensitivity enhancement. In this work, the SPR gold chips were modified using carbon quantum dots (CQDs), graphene quantum dots (GQDs), graphene oxide (GO), chitosan (CS), (CS-CQDs), and (CS-GQDs) thin films. The sensor performance for all layers was analyzed in terms of two aspects, sensitivity and accuracy. The surface morphology and roughness of all films were analyzed using AFM, and the existence of the functional groups in the samples was confirmed using FTIR spectroscopy. Experimental data were fitted to theoretical data formula to characterize the optical properties and thickness of the films. SPR sensor showed sensitivity of 0.138°/pM, 0.332°/nM, 0.215°/pM, 0.195°/nM, 0.169°/pM, and 0.195°/fM using Au/CQDs, Au/GQDs, Au/GO, Au/CS, Au/CS-CQDs, and Au/CS-GQDs bilayer films, respectively. The changes in the spectral bands and peaks intensity of FTIR spectra for all sensing films following DA injection verified DA binding to the sensor surface. AFM analysis showed that the surface morphology and roughness of all films changed as well. The thickness changed by 4.42, 2.59, 2.53, 1.25, 1.63, and 2.28 nm for CQDs, GQDs, GO, CS, CS-CQDs, CS-GQDs layers, respectively. By comparing the performance of all sensor films, SPR sensor based on Au/CS-GQDs exhibited excellent performance with ultra-sensitivity 0.195°/fM, lowest detection limit down to 1 fM of DA was obtained for the first time, RI sensitivity of 10.186°/RIU and the strongest binding affinity of 0.430 × 1015 M-1. Interestingly, Au/GO based sensor exhibited competitive performance to Au/CS-GQDs based sensor with high sensitivity 0.215°/pM, RI sensitivity of 12.402°/RIU, strong binding affinity of 3.279 × 1012 M-1. In addition to high sensitivity, good repeatability, reproducibility, and stability demonstrated for these two sensors, they showed good selectivity to low concentration of DA in the presence of higher concentrations of epinephrin, ascorbic acid, and uric acid. This nanomaterials-based SPR sensor represents an advantageous possibility for diagnosing DA deficiency rapidly, inexpensively with high selectivity and sensitivity. Its utilization as a reliable and economic biomedical diagnostic tool of DArelated brain disorders still be a major goal of research in the field of DA sensors.